Nitrogen doped graphitic carbon from biomass as non noble metal catalyst for oxygen reduction reaction. (September 2019) - Wu, Xiaoxian; Chen, Keqiu; Lin, Zhipeng; Zhang, Yuanming; Meng, Hui
Abstract: This work reports a non noble metal catalyst for the oxygen reduction reaction (ORR) in alkaline. The catalyst is nitrogen doped graphitic carbon synthesized by the pyrolysis of microalgae in ammonia with ferrous chloride as the graphitization catalyst. The morphology, crystalline structure, defects and nitrogen groups of the catalyst are studied to reveal the origin of the high activity in ORR. The mechanism and kinetics of ORR are studied. The nitrogen doped graphitic carbon is more stable compared with commercial Pt/C catalyst. The high performance and low cost of the nitrogen doped graphitic carbon make it a promising candidate for applications in fuel cell and other energy devices. Highlights: Nitrogen doped graphitic carbon is prepared from microalgae as ORR catalyst. Nitrogen and iron carbide contribute to the activity. Comparable activity and higher stability is found compared with Pt/C catalyst.